Tantangan dan Strategi Mendisiplinkan Siswa Berkebutuhan Khusus dalam Pendidikan Inklusif: Tinjauan dari Perspektif Studi Literatur - Tobasa, Majelis Rena; Husna, Difa'ul; Nurjanah, Putria Wati (ANWARUL, 2024)
This research presents a detailed analysis of the challenges faced and the strategies implemented in disciplining students with special needs in the context of inclusive education. The main objective of this research is to summarize the various problems that arise from related literature and to explore the strategies used to address these challenges. The literature study method (library research) is used as the main framework for collecting and analyzing information from various sources such as books, journal articles and other scientific literature. In this analysis, the main focus is aimed at collecting information from various trusted sources in order to understand the essence of the challenges faced in disciplining students with special needs in an inclusive school environment. The main findings of this study reveal the complexity of disciplining students with special needs, requiring a deep understanding of individual needs and close collaboration between educators, school staff, parents, and the community. The results of this analysis also highlight sensitive, responsive and collaborative approach strategies to create an inclusive educational environment for all students. Apart from that, challenges in collaboration between teachers are also an important highlight in strengthening learning approaches for students with special needs. In conclusion, this abstract presents a comprehensive review of the challenges and strategies in disciplining students with special needs in the context of inclusive education. It is hoped that gaining this insight can make a significant contribution to developing a more inclusive and responsive educational environment for all students.